Culm and Leaf Epidermis of Indian Bamboos Pt. IV - oxytenanthera Munro - Agrawal, S. P.; Chauhan, Laxmi (Indian Forester, 1991)
Epidermal features of culm and leaf of Oxytenanthera abyssinica (A. Rich) Munro have been described.